Determinants of neonatal hypoglycemia among neonates admitted at Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia: A retrospective cross-sectional study - Addisu Sertsu; Kabtamu Nigussie; Addis Eyeberu; Abel Tibebu; Abraham Negash; Tamirat Getachew; Adera Debella; Merga Dheresa (SAGE Open Medicine, 2022)
Objective: The study aimed to assess the magnitude and determinants of neonatal hypoglycemia among neonates admitted to the Neonatal Intensive Care Unit at Hiwot Fana Specialized University Hospital, Eastern Ethiopia. Methods: An institutional-based cross-sectional study was conducted among 698 randomly selected neonates at Hiwot Fana Comprehensive Specialized Hospital from 1 January 2018 to 31 December 2020. By looking at the charts, data were gleaned from the medical records. Data were entered into Epi-Data version 3.1 and analysis was performed using SPSS version 22. Bivariable and multivariable logistic regression analyses were conducted to identify determinant factors of neonatal hypoglycemia. Association was described using an adjusted odds ratio along with a 95% CI. Finally, a p -value <0.05 in the adjusted analysis was considered to declare a statistically significant association. Results: Out of 698 neonates, 148 (21.2%; 95% CI: 18.3, 24.5) neonates had hypoglycemia. Preterm birth (AOR = 3.06; 95% CI: 1.02, 9.17), hypothermia (AOR = 2.65; 95% CI: 1.22, 5.75), neonatal sepsis (AOR = 2.61; 95% CI: 1.03, 6.59), diabetic mother (AOR = 2.34; 95% CI: 1.03, 5.33), and delay in initiation of breastfeeding for more than 1 h (AOR = 3.89; 95% CI: 1.17, 12.89) were identified as determinant factors of neonatal hypoglycemia. Conclusion: The magnitude of neonatal hypoglycemia was quite common among neonates. Neonatal hypoglycemia was found to be predicted by preterm birth, hypothermia, neonatal sepsis, maternal diabetes mellitus, and delay in starting nursing. We therefore strongly suggest health-care workers work in the postnatal unit to manage and control these and other determinant factors of hypoglycemia to prevent the occurrence of neonatal hypoglycemia.